Analisis Pengaruh Service Quality dan Electronic Word of Mouth terhadap Purchase Intention dengan Brand Image sebagai Variabel Intervening (Studi Kasus pada Konsumen Dagadu Djokdja) - Bety Hanum Mahira; Ambar Lukitaningsih; Nonik Kusuma Ningrum (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The purpose of this research are to see (1) the impact service quality on purchase intention, (2) the impact electronic word-of-mouth on purchase intention, (3) the impact brand image on purchase intention, and (4) the impact service quality on brand image. (5) the Impact of electronic word-of-mouth on brand image. In selecting samples, researchers used targeted sampling techniques and determined samples based on  criteria established by the researchers. The sample for this study was 150 consumers from Dagadu Yogja. Then check the quality of the data  using validity and reliability tests. After confirming quality, the data are processed through traditional acceptance tests, multiple regression tests, and Sobel tests. Traditional acceptance tests consist of normality, multicollinearity and heteroscedasticity tests. The  data were then analyzed using the certainty test, the split test (t) and the joint test (f).  The results of this study show that (1) service quality has a positive and significant impact on purchase intention, (2) electronic word-of-mouth has a positive and significant impact on purchase intention, and (3) there is a positive and significant impact. is shown. (4) Service quality has a positive and significant impact on brand image (5) Electronic word-of-mouth has a positive and significant impact on brand image.